Treatment and outcomes of metastatic colorectal cancer in Australia: defining differences between public and private practice. Issue 3 (March 2015) - Field, K.; Shapiro, J.; Wong, H.‐L.; Tacey, M.; Nott, L.; Tran, B.; Turner, N.; Ananda, S.; Richardson, G.; Jennens, R.; Wong, R.; Power, J.; et al.
Abstract Background Prior studies have suggested improved outcomes for cancer patients managed in private centres, despite universal healthcare within Australia. Aims To compare patient, disease, treatment and survival data for metastatic colorectal cancer (mCRC) managed in private versus public centres. Methods Analysis of prospectively collected registry data for consecutive patients with mCRC managed at 16 participating centres from July 2009. Results Data for 1065 patients were examined. Age, gender and Charlson comorbidity score were similar for public and private patients. Private patients were more commonly Eastern Cooperative Oncology Group performance score 0–1 (85% vs 78%, P = 0.008), in the highest Index of Relative Socioeconomic Advantage and Disadvantage quintile (57% vs 18%, P < 0.001) or had a single metastatic site (62% vs 54%, P = 0.009). Patients treated in private were more likely to receive chemotherapy (84% vs 70%, P < 0.001), bevacizumab (59% vs 50%, P = 0.008), be treated with curative intent (37% vs 26%, P < 0.001) and undergo metastasectomy (30% vs 22%, P = 0.001). These management differences remained statistically significant after adjusting for baseline characteristics. Management in the private setting was associated with superior overall survival (median 27.9 vs 20 months, hazard ratio 0.7, 95% confidence interval: 0.57 to 0.86, P = 0.001), significant in multivariate analysis adjusting for all baseline covariates. Conclusions Significant differences in baseline characteristics were noted for private versus public patients. However, these do not explain the higher rates of treatment delivery in the private setting, which likely contributed towards the observed survival difference. Further studies are required to determine if the increased likelihood of intervention in the private setting is driven by patient, clinician and/or institutional factors.